Current understanding on antibacterial mechanisms and research progress of tea polyphenols as a supplementary disinfectant for drinking water. (7th November 2022) - Li, Jing; Feng, Cuimin; Jin, Jiyue; Yang, Weiqi; Wang, Zile
Abstract: Disinfection by-products (DBPs) generated during the disinfection of drinking water have become an urgent problem. So, tea polyphenol, a natural green disinfectant, has attracted widespread attention in recent years. This review summarizes the antibacterial mechanism of tea polyphenols and the recent findings on tea polyphenols as disinfectants for drinking water. These studies show that tea polyphenol is an antibacterial agent that works through different mechanisms and can be used as a supplementary disinfectant because of its higher lasting effect and economical cost. The dosage of tea polyphenols as a disinfectant of ultrafiltration effluent is the lowest among all the tea polyphenols disinfection methods, which can ensure the microbial safety of drinking water. This application of tea polyphenols is deemed a practical solution to solving the issue of disinfecting drinking water and reducing DBPs. However, it is necessary to further explore the influence of factors such as pipeline materials on the disinfection process and efficacy to expand the application scope of tea polyphenols. The large-scale application of tea polyphenols still needs to be fine-tuned but with new developments in tea polyphenol purification technology and the long-term need for drinking water that is safe for human consumption, tea polyphenols have good prospects for further development. HIGHLIGHTS: Tea polyphenols are potential disinfectants for drinking water. The antibacterial mechanisms of tea polyphenols are introduced. The research progress on tea polyphenols as a drinking water disinfectant is summarized. Tea polyphenols as a disinfectant for ultrafiltration effluent have unique advantages in reducing DBPs and ensuring the microbiological safety of drinking water. Graphical Abstract